Coping with disassembly yield uncertainty in remanufacturing using sensor embedded products - Mehmet Ilgin; Surendra M. Gupta; Kenichi Nakashima (Journal of Remanufacturing, 2011)
This paper proposes and investigates the use of embedding sensors in products when designing and manufacturing them to improve the efficiency during their end-of-life (EOL) processing. First, separate design of experiments studies based on orthogonal arrays are carried out for conventional products (CPs) and sensor embedded products (SEPs). In order to calculate the response values for each experiment, detailed discrete event simulation models of both cases are developed considering the precedence relationships among the components together with the routing of different appliance types through the disassembly line. Then, pair-wise t-tests are conducted to compare the two cases based on different performance measures. The results showed that sensor embedded products improve revenue and profit while achieving significant reductions in backorder, disassembly, disposal, holding, testing and transportation costs. While the paper addresses the EOL processing of dish washers and dryers, the approach provided could be extended to any other industrial product.
Keywords: 650; disassembly line; experimental design; sensor embedded products; cost-benefit analysis; discrete event simulation; Produkt-Recycling; Produktgestaltung; Messtechnik; Kosten-Nutzen-Analyse